Pan-Islamic International Cooperation and Anticolonialism: South Asia, Turkey, and Southeast Asia - Dr. Arshad Islam (Hamdard Islamicus, 2021)
Non-Western cultures and peoples, such as the Islamic, Hindu, Confucian, and Orthodox Christian, have been systematically oppressed, colonized, and dominated by the ideology, arms, and economies of the West for over two centuries under the imperialist clash of civilizations’. Numerous techniques have been adopted by the oppressed peoples of Asia, Africa, and Latin America to resist this domination, to promote peace, harmony, and stability. One of these strategies that was manifest during the anticolonial movement in South Asia, Turkey, and Southeast Asia was panIslamism. It was relatively forgotten until interest was re-awakened in the Ottoman legacy of Turkey as a leading civilization in Asia and the wider Muslim world. Most modern developed literature is premised on the assumption that western civilization is the model to be aspired by all developing nations. Assistance in economic development is generally assumed as accepting a raft of western neo-imperialist demands that may be contrary to Asian and African cultural mores. In response to this, nationalist movements have become increasingly sceptical about the international development agenda, therefore, Eurasian and South Asian countries such as China, India, Pakistan, Russia, and Turkey are increasingly rejecting subservience to the political and cultural demands of the West. This paper examines the impact of the pan-Islamic cooperation and civilizational exchanges between Turkey, Central Asia, South and Southeast Asia. This is mainly based on Persian, Urdu, English and Dutch sources, focused on the intellectual legacy, achievements, and role of Muslim intellectuals on the unity of the Muslim Ummah against the colonial drive and preserve legacy of caliphate supporting physical and monitory cooperation. This paper also explores the examples of the role of pan-Islamism in resisting European colonialism. It particularly analyses the role of Indian Muslims  in assisting the Ottoman Caliphate, the role of the Ottomans in Sumatran resistance to Dutch colonialism, and the resumption of pan-Islamic ties manifest in modern Turkish disaster relief efforts in Indonesia. Pan-Islamism is already a powerful force in international development. The paper concludes that Pan-Islamic platform offers great scope for developing countries to autonomously assist each other without the shackles of the neo-imperialist agendas, recovering their historical position and dignity as vibrant, compassionate societies